Layanan Bimbingan dan Konseling Bagi Anak Berkebutuhan Khusus dengan Hambatan Fisik dan Motorik - Siti Syaharani Humaira; Hanifatul Muna; Dina Luthfiyyah; Glory Nadine Silalahi; Rizka Andriyani; Jernita Butar-Butar (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
Guidance is the process of providing assistance carried out by someone who is an expert or a counselor to another person or counselee in a sustainable way so that they are able to understand all the potential that exists in themselves and are able to understand their environment, are able to accept themselves and can adapt. Children with special needs (Heward) are children who experience deviations, disorders or disabilities in physical, mental, emotional and social terms, or a combination of these things in such a way that they require special educational services, which are adapted to the deviation, disorder or their disability.